Z-scheme g-C3N4 nanosheet photocatalyst decorated with mesoporous CdS for the photoreduction of carbon dioxide. Issue 12 (15th June 2021) - Mkhalid, Ibraheem A.; Mohamed, Reda M.; Ismail, Adel A.; Alhaddad, Maha
Abstract: Herein, novel mesoporous CdS nanoparticle (NP)-incorporated porous g-C3 N4 nanosheets with large surface areas and varying CdS NP percentages were constructed for the first time. The synergistic effect of mesoporous CdS NPs and porous g-C3 N4 nanosheets indicated effective charge carrier separation and promoted CO2 photoreduction to form CH3 OH upon illumination. The highest yield of CH3 OH over 3% CdS-g-C3 N4 heterostructures was determined to be approximately 1735 μmol g −1, which was 3.8- and 5.50 times greater than those of mesoporous CdS NPs and pristine g-C3 N4 nanosheets, respectively. In addition, the mesoporous 3%CdS-g-C3 N4 heterostructure showed an outstandingly enhanced CO2 photoreduction rate of 192.7 μmol g −1  h −1, which was estimated to be ~4.1 and 5.9- times better than CdS (47.1 μmol g −1  h −1 ) and pristine g-C3 N4 (32.6 μmol g −1  h −1 ), respectively. The photoreduction performance was retained at approximately 94.7% after five cycles of illumination for 45 h. The remarkable synthesized mesoporous CdS-g-C3 N4 heterostructure played an essential role, with its narrow bandgap and high surface area enabling improved photoinduced carrier separation and a widened range of light absorption. A plausible mechanism for CO2 photoreduction by the mesoporous CdS-g-C3 N4 heterostructure was proposed and verified by photoelectrochemical and photoluminescence measurements.